Innovative and Sustainable Information Services for Moldovan Higher Education: Evaluation of Moldavian Libraries System - Landoy, Ane; Ghinculov, Silvia; Repanovici, Angela; Cheradi, Natalia (Qualitative and Quantitative Methods in Libraries, 2017)
Within the project Innovative and Sustainable Information Services for Moldovan Higher Education, research was conducted on development and further education opportunities for librarians in the Moldovan universities. The goal of the research was to identify the level of education, training and information needs, the level of satisfaction of librarians on human resource management within these libraries, the level of knowledge and the intent to improve. The research method was a survey through a self-administrated questionnaire provided online by Survey Monkey. The level of satisfaction/dissatisfaction of the librarians within the Moldovan library system matches their expectations. Although the awareness of the librarian’s importance becomes increases in the library system, recognizing the right to training and development, changing the mentality seem promising..